2019
DOI: 10.1137/18m1201858
|View full text |Cite
|
Sign up to set email alerts
|

Regularity Issues for Cosserat Continua and $p$-Harmonic Maps

Abstract: For minimizers in a geometrically nonlinear Cosserat model for micropolar elasticity of continua, we prove interior Hölder regularity, up to isolated singular points that may be possible if the exponent p from the model is 2 or in ( 32 15 , 3). The obstacle to full continuity turns out to be the existence of certain minimizing homogeneous p-harmonic maps to S 3 . For those, we slightly improve existing regularity theorems in order to achieve our result on the Cosserat model. MSC 2020. 58E20; 74G40; 74B20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…In a recent paper Gastel [6] was exploiting the connection between the theory of Cosserat micropolar elasticity and p-harmonic maps. He showed that the only obstacle for the regularity of minimizers in a geometrically nonlinear Cosserat model for micropolar elasticity of continua is the possible existence of non-constant p-minimizing tangent maps from B 3 into S 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper Gastel [6] was exploiting the connection between the theory of Cosserat micropolar elasticity and p-harmonic maps. He showed that the only obstacle for the regularity of minimizers in a geometrically nonlinear Cosserat model for micropolar elasticity of continua is the possible existence of non-constant p-minimizing tangent maps from B 3 into S 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Among many variants and vast body of results of Cosserat theory available in the literature, P. Neff [5,6,7] has made some systematical analysis of the Cosserat theory for micropolar elastic bodies by establishing the existence of minimizers in the framework of calculus of variations. Very recently, in an interesting article [8], Gastel has shown a partial regularity theorem of minimizing weak solutions to a Cosserat energy functional for microplar elastic bodies.…”
Section: Introductionmentioning
confidence: 99%
“…By extending the techniques in the study of minimizing p-harmonic maps by Schoen-Uhlenbeck [13], Hardt-Lin [9], Fuchs [10], and especially Luckhaus [11], Gastel has recently shown in an interesting article [8] that any minimizer (φ, R) ∈ H 1 (Ω, R 3 )×W 1,p (Ω, SO(3)) of the Cosserat energy functional Coss(φ, R) of the Cosserat functional (1.1) belongs to C 1,α × C α in Ω away from a singular set Σ of isolated points for all 2 ≤ p < 3. Moreover, Σ is shown to be an empty set when p ∈ [2, 32 15 ] by extending stability inequality arguments by Schoen-Uhlenbeck [14], Xin-Yang [15], and Chang-Chen-Wei [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations